Development of mini smart multipurpose vehicle for organic rice harvesting - Kanchana Daoden; Sureeporn Sringam; Supanat Nicrotha; Thanawat Sornnen (Institute of Advanced Engineering and Science, 2022)
This research aimed to develop the mini smart multipurpose vehicle (MSMPv) innovative from the conventional agriculture tractor for three objectives. The novel automatic gear modified technique for the MSMPv is proposed, then an idea to enhance peripheral capability through a hitch system. The final purpose is to support the farmer's ability to follow organic agriculture regulations on the issue of contaminated tools and machinery, especially in the rules related to contamination of equipment or machines that cannot share with conventional agricultural production. The organic rice crop plot of Nong Bua Lamphu Province in Thailand has been set to the case study. Here, farmers faced problems; lack of labour, production under an organic system that does not permit chemicals, and limited harvesting. According to the existing technology, this research has developed a typical farm tractor used in the country by inventing a manual transmission engine to an automatic transmission and accessories such as remote control, GPS, camera, and sensors. Thus, the development of this organic rice harvesting prototype should be an approach that provides both the opportunity to raise the self-reliance concept and enhance the knowledge of the development of innovative tools for farmers simultaneously.